2002
DOI: 10.3354/meps236075
|View full text |Cite
|
Sign up to set email alerts
|

Temporal abundance patterns of the red tide dinoflagellate Noctiluca scintillans along the southeast coast of Australia

Abstract: . Peaks in abundance of up to 79 cells l -1 were observed, at the same time or subsequent to diatom blooms which were caused by episodic uplifting events during the spring and summer. The diatom blooms were dominated by the small centric diatom Thalassiosira partheneia, which was also the dominant food item found within the Noctiluca cells. A high proportion (> 80%) of Noctiluca cells contained food particles in their vacuoles during the diatom blooms, suggesting that the increase in abundance of Noctiluca was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 22 publications
2
12
0
3
Order By: Relevance
“…Many studies have shown that N. scintillans feeds mainly on phytoplankton, particularly diatoms (Schaumann et al, 1988;Umani et al, 2004;Harrison et al, 2011;Zhang et al, 2016). N. scintillans blooms are also known to co-occur with diatom blooms Nakamura, 1998;Tiselius and Kiørboe, 1998;Dela-Cruz et al, 2002). Euplotes sp., which are in the ciliate order Hypotrichida, are common in both freshwater and marine habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that N. scintillans feeds mainly on phytoplankton, particularly diatoms (Schaumann et al, 1988;Umani et al, 2004;Harrison et al, 2011;Zhang et al, 2016). N. scintillans blooms are also known to co-occur with diatom blooms Nakamura, 1998;Tiselius and Kiørboe, 1998;Dela-Cruz et al, 2002). Euplotes sp., which are in the ciliate order Hypotrichida, are common in both freshwater and marine habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Temperatures ranging from (22~24) ℃ and (20~24) ℃ were also found to be optimum for Noctiluca at various regions (Uhlig and Shaling, 1985). Diatoms availability was found to be an important factor to generate the Noctiluca scintillans blooms as these blooms are documented to occur after diatom blooms (Dela-Cruz et al, 2002;Elbrächter and Qi, 1998;Tiselius and Kiorobe, 1998). However, we have not observed blooms of diatoms in this study prior to the Noctiluca scintillans blooms.…”
Section: Discussionmentioning
confidence: 99%
“…The red tides have been observed over a wide range of the coast (30-36°S), although greater than 90% were observed off Sydney, Australia's largest city (Ajani et al, 2001;Dela-Cruz et al, 2003). Previous field studies have indicated that the abundance of Noctiluca in Sydney's coastal waters is highest during the spring and summer (Murray & Suthers, 1999;Dela-Cruz et al, 2002). Specifically, peaks in abundance were found to coincide with periods of upwelling, which stimulate blooms of phytoplankton that Noctiluca consumes (Dela-Cruz et al, 2002).…”
Section: Introductionmentioning
confidence: 94%
“…The study was conducted in the austral spring and summer, when the abundance of Noctiluca is relatively high (Murray & Suthers, 1999;Dela-Cruz et al, 2002), and also when the EAC has its strongest flows (Middleton et al, 1997). Samples were collected in November 1998 (austral spring) and January 1999 (austral summer), aboard two cruises on the National Facility Research Vessel, Franklin.…”
Section: Location and Time Of Studymentioning
confidence: 99%
See 1 more Smart Citation